TANGGAPPERTUMBUHANSTUMP MATA TIDURKARET TERHADAP KOMPOSISI MEDIA TANAM DAN PEMUPUKAN NPK ORGANIK - Mahfriza Fansuri Mahfriza FansuriQ; Irsa Irsa; Nini Rahmawati (Jurnal Agroekoteknologi, 2013)
The aim of the research is to know the response of rubber budded stump growth of the compositionsof growing media and organic NPK fertilization. It was conducted at Kuala Bingai Village, Stabat,regency of Langkat about 15 m sea level on May to August 2012 by using arandomized blockdesignfactorialtwofactorsthat is organic NPK fertilization (0, 50, 100, 150 g/polybag) and thecomposition of growing media (subsoil, subsoil+compost of blotong sugar cane andsubsoil+compost of blotong sugar cane+sand). The parameters observed were percentage stump ofshoot, speed of eye stump out, shoot lenght,number of leaves, shoot grith, percentage of stump oneumbrella leaf’s and total leaves width.The result of research showed that compositions of growthmedia and organic NPK fertilization showed no significant effects for all parameters. Interaction ofboth treatments influenced significantly on shoot lenght 8 and 12 MST and shooth grith 6-10 MST.Key words : organic NPK, growing media, rubber budded stump